A Numerical simulation of delamination caused by internal gas pressure for mid-density CFRP. (December 2018) - Koyanagi, Jun; Shinba, Kenta; Fukuda, Yasuhiro; Hirai, Kenichi; Nakazato, Akiko; Yoshimura, Akinori; Aoki, Takuya; Kogo, Yasuo
Abstract: Interlaminar debonding (delamination) is a major problem for carbon fiber-reinforced plastic (CFRP) when it is used in thermal protection systems subjected to rapid heating, such as in a re-entry situation. In this study, the possibility of avoiding delamination by controlling material porosity was investigated experimentally and numerically. CFRP specimens having various initial porosities (mid-density CFRP) were prepared and rapid heating tests (∼6 MW/m 2 ) were performed, and the specimens were examined to determine whether delamination had occurred. To predict the delamination, heat transfer and pyrolysis gas-induced internal gas pressure growth were simulated numerically as a function of heating time. The parameters regarding temperature-dependent chemical reaction rate, orthotropic coefficients for gas permeability, and flatwise tensile strength were determined by individual experiments using the CFRP specimens. The coupled analysis of thermal transfer and pyrolysis gas flow following Darcy's law was conducted by finite-difference form, employing the experimentally obtained parameters. When the gas pressure exceeds the flatwise tensile strength of CFRP, delamination is assumed to occur. The numerical results show good agreement with the experimental results, and it is concluded that delamination can be eliminated by using mid-density CFRP.